GROWING UP HEALTHY: A STUDY ON FEEDING PRACTICES AND NUTRITIONAL WELL-BEING IN DAYCARE-ATTENDING CHILDREN (6-23 MONTHS) IN KIRINYAGA COUNTY - Otieno , Beatrice Akinyi; Macharia, Samuel Kiprono (American Research Journal of Nursing and Health Sciences (ARJNHS), 2024)
Childhood nutritional status serves as a key indicator of overall well-being and health, with infant and young child feeding practices emerging as pivotal interventions for enhancing child health and nutrition, as highlighted by Muluye et al. (2020). This study delves into the intricate relationship between a child's nutritional status, influenced by food intake quantity and quality, and its profound impact on growth, development, and physical activity. The assessment of nutritional status in children under five commonly relies on anthropometric measurements, encompassing length/height, weight, and mid (upper) arm circumference, juxtaposed against established national and international standards, as articulated by De Onis (2006) and WHO (2011). Anthropometry stands out as a critical method for discerning a child's nutrition status, providing insights into potential growth and health concerns. However, the key to unlocking optimum growth lies in the quality of care bestowed upon infants and young children. This paper emphasizes that achieving optimal growth necessitates a comprehensive consideration of the child's characteristics, needs, and developmental levels in daily childcare practices, aligning with the insights offered by Dewey and Brown (2003). As we navigate the nuanced landscape of childhood nutrition, this research seeks to contribute a holistic understanding of the interplay between feeding practices, nutritional status assessment, and childcare quality. The findings aim to inform strategies and interventions that promote not only physical health but also holistic development in children under five. By exploring these facets, the study endeavors to lay the groundwork for enhanced healthcare practices, ensuring a more comprehensive and nuanced approach to childhood nutrition that extends beyond conventional anthropometric measurements.